Gold-Polypyrrole-Loaded Eosin in Photo-Mediated Treatment of Hidradenitis Suppurativa: In Vivo Trans-Epidermal Permeation Study and Clinical Case Report - Abdullah I. El-Kholy; Maha Fadel; Maha Nasr; Ibrahim El-Sherbiny; Abeer Tawfik; Yasser O. Mosaad; Doaa Abdel Fadeel (MDPI AG, 2022)
This study reports a new protocol for the management of Hidradenitis Suppurativa (HS), depending on the synergistic photodynamic and photothermal effect of eosin yellow-gold-polypyrrole hybrid nanoparticles (E-G-Ppy NPs). E-G-Ppy NPs and gold-polypyrrole NPs (G-Ppy NPs) were synthesized, characterized, and formulated in topical hydrogels. Then, in vivo trans-epidermal permeation study, under both dark and white light-irradiation conditions, was done on albino mice. The E-G-Ppy hydrogel was then applied on a twenty-four years old female with recurrent axillary HS lesions pretreated with fractional CO2 laser. Thereafter, the treated lesions were irradiated sequentially, using an IPL system, in the visible (~550 nm) and NIR band (630-1100 nm) to activate the synthesized nanoparticles. Results showed that, upon application to mice skin, E-G-Ppy exhibited good tolerance and safety under dark conditions and induced degenerative changes into dermal layers after white-light activation, reflecting deep penetration. Photo-activation of E-G-Ppy hydrogel to a severe Hidradenitis Suppurativa case showed an improvement of 80% of the lesions according to average HS-LASI scores after 4 sessions with no recurrence during a follow-up period of six months. In summary, the dual photodynamic/photothermal activation of E-G-Ppy NPs can represent a promising modality for management of HS. Further expanded clinical studies may be needed.